Objective measurement of Akodon budini dorsal coloration: methodological concerns - Sandoval Salinas, Maria Leonor (2016)
The role of color in taxonomic and systematic studies of several taxa is central. Color data are more valuable if they permit comparisons. We aimed to provide pelage objective color measurements of a series of Akodon budini and to use those color data to test and to quantitatively analyze the influence of both the lighting source and the measuring point, in the determination of pelage color of museum skins. We used a spectroradiometer to measure the pelage color at five points over the dorsal midline of 54 Akodon budini museum skins. PCAs and ANOVAs were conducted over the color data. The characteristics of the studied series also allowed us to include and assess the potential effects of some main sources of intra-specific variation. Determinations of fur color strongly depend on the lighting source, and therefore it is essential that lighting conditions are controlled during color measurements and then made explicit when communicating the color characterization of particular taxonomic units. Furthermore, color determinations strongly depend on the measuring point, even on the same body area, and therefore it is critical that the color characterization of a taxon includes the variation between different points of the different body parts of the studied specimens.